2012
DOI: 10.1890/120007
|View full text |Cite
|
Sign up to set email alerts
|

A framework for engaging diverse communities in citizen science in the US

Abstract: Citizen science is a powerful tool for connecting people to science, but in the US, such initiatives have not connected as well to groups that have been historically underrepresented in science. Research suggests that while several factors contribute to this lack of diverse participation in citizen science, the critical hurdle may be an absence of alignment between community priorities and research objectives. Here, I discuss a participatory framework for designing citizen‐science programs that align with comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
208
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(211 citation statements)
references
References 14 publications
2
208
0
1
Order By: Relevance
“…However, experience has shown that different segments of the population are more prone to participate than others (Soleri et al 2016). Both Hobbs and White (2012) and Pandya (2012) note that citizen scientists currently tend to be whiter, older and more middle-class than broader society; a similar pattern is found in volunteering in general (Measham and Barnett 2008). For instance, in their study of the Second Southern African Bird Atlas Project, Wright et al (2015Wright et al ( , pp.…”
Section: Who Is the Citizen Scientist?mentioning
confidence: 99%
“…However, experience has shown that different segments of the population are more prone to participate than others (Soleri et al 2016). Both Hobbs and White (2012) and Pandya (2012) note that citizen scientists currently tend to be whiter, older and more middle-class than broader society; a similar pattern is found in volunteering in general (Measham and Barnett 2008). For instance, in their study of the Second Southern African Bird Atlas Project, Wright et al (2015Wright et al ( , pp.…”
Section: Who Is the Citizen Scientist?mentioning
confidence: 99%
“…Such efforts have yielded valuable data, led to scientific discoveries, and brought more non-professionals into the research process ). However, current citizen science participants do not reflect US demographics, with historically underserved populations continuing to be underrepresented (Pandya 2012). Although data are lacking, indications are that demographic profiles of citizen science participants reflect the imbalance among those pursuing higher education in the fields of Science, Technology, Engineering, and Math (Campbell 2002, Jolly 2002, and those in science professions (Fig.…”
Section: What's the Problem?mentioning
confidence: 99%
“…2). While opportunities to enhance the quality of public engagement exist across this spectrum, in our symposium we focused on the community-driven (Pandya 2014), co-created end as offering some of the greatest promise as well as greatest challenge for engagement with underserved communities (Pandya 2012). In this essay we provide a brief overview of the problem we were addressing and report the observations and suggestions made by symposium participants in the café.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding motivation is also a critical prerequisite to developing successful CS and crowdsourcing projects and is an area of active research [8], [9], [41]- [44]. Based on these studies (which are situated mostly in the fields of ecology, biology and nature conservation), a summary of different volunteer motivations includes: the desire to learn more about the science behind the project; helping the environment; getting to know other people with similar interests and as a way to make new friends; feeling like an active participant and co-owner of the project; relevance to the community; ability to see the impact of their work, e.g.…”
Section: Recruitment Motivation and Incentives For Participation mentioning
confidence: 99%